2010
DOI: 10.1074/jbc.m109.061168
|View full text |Cite
|
Sign up to set email alerts
|

Native-unlike Long-lived Intermediates along the Folding Pathway of the Amyloidogenic Protein β2-Microglobulin Revealed by Real-time Two-dimensional NMR

Abstract: ␤2-microglobulin (␤2m), the light chain of class I major histocompatibility complex, is responsible for the dialysis-related amyloidosis and, in patients undergoing long term dialysis, the full-length and chemically unmodified ␤2m converts into amyloid fibrils. The protein, belonging to the immunoglobulin superfamily, in common to other members of this family, experiences during its folding a long-lived intermediate associated to the trans-to-cis isomerization of Pro-32 that has been addressed as the precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 28 publications
4
61
0
Order By: Relevance
“…7b). 22,46 This observation indicates that these residues might prefer to form the native structure even at low pH, deviating from the ideal two-state transition between the acid-denatured state and urea-unfolded state. Thus, the correlations of these residues do not gather on the diagonal line.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…7b). 22,46 This observation indicates that these residues might prefer to form the native structure even at low pH, deviating from the ideal two-state transition between the acid-denatured state and urea-unfolded state. Thus, the correlations of these residues do not gather on the diagonal line.…”
Section: Discussionmentioning
confidence: 92%
“…It is reported that the folding intermediate with transPro32 (denoted as I T ) is in an amyloidogenic state at this pH. [22][23][24][25][26] Eichner et al reported the structure of ΔN6-β2m, which is thought to be a mimic of I T . 24 The deletion of the N-terminal residues induces restructuring around Pro32 and subsequent structural fluctuations.…”
Section: Introductionmentioning
confidence: 96%
“…Characterization of these structures and the factors involved in their stability would provide an insight to understand how and when various forces come into play in directing protein folding [1][2][3][4]. The development of a broad range of techniques has led to the identification and characterization of stable intermediates in several proteins [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The ANS fluorescence was measured using a Hitachi F-7000 spectrofluorometer at 25°C with excitation at 350 nm and emission at 400 -600 nm. 3 ) and Western Blot Analysis-The reaction mixture containing 0 or 12.5 M ␤2-m, 0 or 0.63 M ␣2M, 50 mM citrate buffer (pH 4 -5) or phosphate buffer (pH 6 -7.5), 100 mM NaCl, and 0 -0.5 mM SDS or 0 -100 g/ml heparin was incubated for 1 h at 25°C. BS 3 (Thermo Fisher Scientific), an amine-reactive cross-linking reagent, was then added at a final concentration of 5 mM to the mixture.…”
Section: Methodsmentioning
confidence: 99%
“…amyloid fibrils is thought to be induced by partial unfolding of ␤2-m (3,4). Several groups have established conditions under which ␤2-m amyloid fibril formation occurs at a neutral pH (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%